OPTIMIZING LOCAL NETWORK SYSTEM - Andy Johnny HP; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 1999)
Communication is a very basic requirement for human beings, without any communication that men will not receive any information. Where communication is the exchange of information between the person with someone else, which are both active with each other to convey something to know each other. as well as in a  computer network, information is something that is very basic, this information will be used jointly by one or several people. Even this information is a very high value and useful to the users, as well as in the business world then this information is a reference for future business development backwards. As well as information about product info that will experience a high selling price, about the increase in foreign exchange rates, on the development of future business and about the opportunity to instill an investment within and outside the country. Similarly, in education, hence the existence of a computer network we will find out information about science and technology are developing at present, and new discoveries in technology. And this information  will be obtained on- line without any time limit.